2023
DOI: 10.3390/agronomy13030691
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate Fertilizers Increase Nutrient Absorption Efficiency and Agro-Physiological Properties of Lettuce Plant

Abstract: The extensive use of chemical fertilizers is responsible for numerous environmental problems including low food quality, soil degradation, and toxicity to beneficial living organisms in the soil. Nano-fertilizers (NFs) application may be a promising solution for combat these challenges. The current study focused on the efficiency of applying small amounts of NFs incorporated with conventional nitrogen, phosphorus, and potassium (NPK) fertilizers to reduce the quantities of conventional fertilizers (CFs) in let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Application of zinc (Zn) and silicon (Si) decreases water stress [18,[20][21][22]. Under water stress, both elements play vital roles in the improvement of organic osmolyte accumulation, water balance in plants, rate of photosynthesis, stomata movements, production of endogenous phytohormones, nutrient uptake, accumulation of primary and secondary metabolites which eventually promote the plant growth of plants, biomass accumulation, as well as yield quantity and quality [20,23]. At the same time, many scientific reports confirmed that these elements (Si and Zn) significantly reduced the activity level of reactive oxygen species (ROS) and improved the total antioxidant activity and activity levels of antioxidant enzymes under environmental stresses such as drought stress [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Application of zinc (Zn) and silicon (Si) decreases water stress [18,[20][21][22]. Under water stress, both elements play vital roles in the improvement of organic osmolyte accumulation, water balance in plants, rate of photosynthesis, stomata movements, production of endogenous phytohormones, nutrient uptake, accumulation of primary and secondary metabolites which eventually promote the plant growth of plants, biomass accumulation, as well as yield quantity and quality [20,23]. At the same time, many scientific reports confirmed that these elements (Si and Zn) significantly reduced the activity level of reactive oxygen species (ROS) and improved the total antioxidant activity and activity levels of antioxidant enzymes under environmental stresses such as drought stress [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Only a 32.3-ton ha −1 decrease was found when using magnesium chelate treatment; therefore, nMgO treatments were used for green-onion yield [58]. Generally, the increase in the yield quantity of treated onion plants with nMgO fertilizers rather than other utilized fertilizers might be associated with the properties of Mg nanoparticles, which are characterized by a smaller size, higher absorption, and more ease of attachment than other forms of magnesium [59,60]. In addition, the findings of the current study are similar to those found by [16], where foliar application with magnesium nano-fertilizers significantly increased the crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the food we eat every day is in the form of biological molecules, and plants absorb little molecules consisting of nitrogen, phosphorus, and potassium to build bigger molecules such as sugars, oils, and proteins. The macro element N/P/K fertilizers were the most-used during crop planting in China, but a missing single nutrient will not be able to produce all of the large molecules in plants [39]. The fertilizer ratio affects crop yield, quality, and nutrition composition [40].…”
Section: Chemical Fertilizers and Crop Cultivationmentioning
confidence: 99%